Traumatic ulnar nerve dislocation: an unusual entity - Benabbouha, Abdellatif; Rifki, Faycal; Sallahi, Hicham; Mergad, Omar (International Journal of Research in Orthopaedics, 2022)
Ulnar nerve dislocation is defined as abnormal movement of the ulnar nerve at the elbow joint. This dislocation has been reported in 16% of asymptomatic arms. However, posttraumatic ulnar nerve subluxation remains a rare clinical entity. We present a unique case of posttraumatic ulnar nerve dislocation and describe clinical characteristics and etiology of this injury and how it was managed.